The Effect of Age and Gender on the Relative Fatigability of the Human Adductor Pollicis Muscle - Ditor, David S. (My University, 1999)
The purpose of this study was to examine the relationships between age, gender and fatigue resistance, and further, to determine the relative influence that estrogen status, membrane excitability, absolute force and muscle length have over the development of fatigue. A total of 48 subjects, classified by age and gender participated in this study; 12 young males (25.3 ± 2.1 yrs.), 12 young females (23.5 ± 2.1 yrs.), 12 elderly males (71.7 ± 5.6 yrs.) and 12 elderly females (69.5 ± 4.6 yrs.). The young females were all eumenorrheic, not taking oral contraceptives and tested in the mid-follicular phase of the menstral cycle. None of the elderly females were on hormone replacement therapy. A 3 minute paradigm of intermittent maximal voluntary contractions (MVC) was used to fatigue the adductor pollicis muscle, in which 5s MVC's were alternated with 2s rest periods. In addition, maximal twitches were evoked in each 2s rest period. No gender difference in fatigability was evident between young males and young females when considering the fatigue index of the evoked twitch (FI-PT) (young males: 39.8 ± 26.7%, young females: 36.6 ± 19.0%). There was also no gender difference in fatigability found between elderly males and elderly females when considering the FI-PT (elderly males: 24.9 ± 26.6%, elderly females: 16.4 ± 48.9%). However, potentiation of the evoked twitches during fatigue may have confounded these measures. When considering the changes in voluntary force during fatigue, there was a strong trend for a gender by time interaction between young males and young females.(p=0.06), which suggests that the former were more fatigable. The trend for this gender difference was also apparent in the voluntary fatigue index (FI-MVC) (young males: 44.7 ± 10.5%, young females: 37.8 ± 14.1 %; p=0.12). Similarly, young males had a significant decrease in M-wave amplitude during the fatigue protocol and a trend for a decrease in M-wave area (p=0.08), while young females showed no significant decreases in either M-wave measure during the fatigue protocol. There was no gender difference found between the elderly males and elderly females when considering the FI-MVC (elderly males: 24.2 ± 10.7%, elderly females: 26.3 ± 14.5%). Both groups also showed small but significant reductions in theM-wave amplitude during the fatigue protocol, although M-wave area was well maintained. The fact that a strong trend for a gender difference in fatigability was found in the young subjects but not the elderly subjects, suggests that estrogen may possess fatigue resisting properties, even during short duration exercise in which glycogen depletion is not a concern. With respect to the age-related differences in fatigue, elderly males were found to be significantly more fatigue resistant than young males as indicated by the FI-MVC (p<0.01), and the significant age by time interaction during the fatigue protocol (p<0.01). In contrast, only a trend was found for an age by time interaction between the young and elderly females during the fatigue protocol (p=0.06). This trend for an age-related difference in fatigue amongst women was also reflected in the FI- MVC (p=0.13).
Keywords: fatigue resistance, mid-follicular phase, voluntary contractions